2016
DOI: 10.1186/s13568-016-0268-y
|View full text |Cite
|
Sign up to set email alerts
|

Whole resting cells vs. cell free extracts of Candida parapsilosis ATCC 7330 for the synthesis of gold nanoparticles

Abstract: The cell free extracts of Candida parapsilosis ATCC 7330 are more efficient than the whole resting cells of the yeast in the synthesis of directly usable gold nanoparticles as revealed by this systematic study. Cell free extracts yielded gold nanoparticles of hydrodynamic diameter (50–200 nm). In this study, the total protein concentration influences the nanofabrication and not only the reductase enzymes as originally thought. Powder X-ray diffraction studies confirm the crystalline nature of the gold nanopart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 71 publications
1
6
0
Order By: Relevance
“…For example, the spectrum of gPdNPs has a peak at 390 nm (Figure 1), which is specific for PdNPs [18,61]. A peak of gAuNPs in the range 525-590 nm is specific for chemically-synthesized AuNPs of different sizes, according to data reported in the literature [8,12,13,19,38,42,43,48] as well as our results [56,62]. The color, size and shape of AuNPs and gAuNPs are dependent on the NPs' synthesis conditions: culture liquid of a 1-day culture incubated for 3 days with HAuCl 4 produces a dark blue solution of small gAuNPs with a peak at 525 nm.…”
Section: Characterization Of the Green-synthesized Nanoparticlessupporting
confidence: 63%
See 2 more Smart Citations
“…For example, the spectrum of gPdNPs has a peak at 390 nm (Figure 1), which is specific for PdNPs [18,61]. A peak of gAuNPs in the range 525-590 nm is specific for chemically-synthesized AuNPs of different sizes, according to data reported in the literature [8,12,13,19,38,42,43,48] as well as our results [56,62]. The color, size and shape of AuNPs and gAuNPs are dependent on the NPs' synthesis conditions: culture liquid of a 1-day culture incubated for 3 days with HAuCl 4 produces a dark blue solution of small gAuNPs with a peak at 525 nm.…”
Section: Characterization Of the Green-synthesized Nanoparticlessupporting
confidence: 63%
“…Many plants [11,12,21,[24][25][26], algae [4], microorganisms [1,3,[7][8][9][10]14,18,23,[27][28][29][30], as well as redox-imbalanced mammalian cells and systems [31] are known to produce nanostructured mineral crystals and metallic NPs with properties similar to chemically-synthesized materials. Biological agents, including polysaccharides, polypeptides, DNA, enzymes secreted by cells [24,[32][33][34][35][36][37][38][39][40][41] and purified enzymes [42,43] are able to reduce noble metal ions to gain metallic NPs. Besides the practical aim of gNPs production, investigations on the green synthesis processes will be useful for elucidating the mechanisms of cells' responses to stress caused by metal ions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This makes this reaction more attractive from an economic point of view. Compared to previous attempts, this is the first efficient enzymatic access to produce hydroxyketone 3 , which itself represents a valuable building block for syntheses of compounds against immune disorders, viral and neurological diseases. Compared to our successful monoreduction of 2 (route A), no KRED was identified having activity towards 4 which prompted us to discard route B (Scheme ).…”
Section: Resultsmentioning
confidence: 60%
“…Krishnan et al have reported that gold nanoparticles biosynthesized using the cell-free extract of yeast Candida parapsilosis ATCC 7330 showed improved dispersion of gold nanoparticles in a pH 12 solution [12]. These dispersed nanoparticles (32 nm) demonstrated their size-dependent catalytic activity for the reduction of 4-nitrophenol to 4-aminophenol using sodium borohydride (Scheme 1) as a hydride source with an apparent rate constant of 0.138 min À1 and normalized rate constant (k nor ) of 4.18 x 10 7 mol À1 min À1 .…”
Section: Catalytic Performance Of Gold Nanoparticles Prepared From MImentioning
confidence: 99%